Physical Fitness and Locomotor Skills in Children With Esophageal Atresia-A Case Control Pilot Study - König, Tatjana T.; Muensterer, Oliver J. (Frontiers in Pediatrics, 2018)
Background Patients with esophageal atresia (EA) often experience physical limitations. With increasing survival over the past decades, the focus in care shifted towards improving the long-term quality of life. We performed validated testing fitness and motor skills in children born with EA. Methods Patients with EA were evaluated using the standardized Kinderturntest Plus/ Deutscher Motorik Test after caregiver’s written consent. Test scores range from 1 to 5 (compared to an age- and gender matched standard population). Caregivers completed an online-questionnaire on patient history. Results Seventeen patients (median age 7 [3-12] years) were included. Comorbidities were prematurity (54%), birth weight <1500g (23%), congenital heart disease (46%), developmental delay (38%), skeletal deformity (23%), and anorectal malformation (15%). The mean test score was significantly lower in children with EA (2.19) compared to a control group matched for age, gender, body weight and –height, (2.75, p=0.04), and the general population (3, p=0.00). Distribution of patient scores was below the 41st performance percentile for gender and age in 54%-63%. Caregivers identified notable deficits of strength and endurance. All but one patient complained about discomfort during physical exercise, most commonly respiratory distress (46%) and gastroesophageal reflux symptoms (31%). Notably, 93% of subjects participated in regular school physical education classes, and 86% participated regularly in additional organized sporting activities. Conclusions Children after EA repair have decreased physical fitness and impaired locomotor function compared to the general population on a standardized test. Physical discomfort is frequent during exertion. To avoid demotivation, locomotor skill should be promoted at each individual’s comfortable level. The study was registered at www.researchregistry.com (No. 3707).